Case Series Study of Visual Field Defects in Pituitary Gland Tumors - Vallabha K; Vijayamahantesh M. Bijapur (Al Ameen Medical College, 2017)
Background: The pituitary gland is a small endocrine gland, weighing about 500 mg. Pituitary adenomas account for 12-15 % of all intracranial tumors. Pituitary gland is in the sella turcica, 8-13 mm lower than the optic chiasm. Therefore, when it increases, it can easily compress the optic nerve fibers in the chiasm. Micro adenomas can have a negligible effect on the visual system or on the function impairment when pituitary adenoma compresses the frontal part of optic nerve; impairments in visual fields, visual acuity, and color contrast sensitivity are possible. The long standing compression of the chiasm induces primary optic nerve atrophy, which directly impairs visual function. The prevalence of visual field defects in pituitary adenomas varies from 37 to 96% in different studies. Because of its anatomical relationship with optic chiasm, pituitary adenoma typically results in bitemporal hemianopia. However, according to the tumor size and optic chiasmal position, a variety of field defects can be produced by pituitary adenoma and the tumor size is a significant factor in the severity of Visual field defects. Aim: To study the proportion of patients with visual field defects in pituitary adenomas and to study the pattern of visual field defects in pituitary adenomas. Materials and Methods: 7 patients diagnosed with a pituitary adenoma underwent complete ophthalmic and Humphrey's Perimetry 30-2 visual field test at Department of Ophthalmology, BLDEU'S Shri B M Patil Medical College Hospital, Vijayapura between January 2015 to December 2015. Results: Among the 7 cases in the study, 2 cases were of pituitary micro adenoma constituting 28.5% and the remaining cases (5 cases) were pituitary macro adenoma, constituting 71.5%. Visual acuity of 6/6 - 6/12 were observed in 10 (71.4%) out of total 14 eyes. Visual field defects were observed in all 6 cases (85.7%). Bilateral temporal hemianopia was observed in the majority (42.8%) of cases with field defects. One eye blind and contra lateral temporal hemianopia was observed in 14.2%. One eye temporal hemianopia and other eye involvement of 3 quadrants seen in 1 patients (14.2%). 1 patients had no visual field defects. Conclusion: Although ophthalmologists have a minor role in primary diagnosis of pituitary adenoma, routine ophthalmologic examination is very important. To detect early visual field defects, automated perimetry should be done as a part routine examination in patients with suspected pituitary adenoma.